2014
DOI: 10.1016/j.ssi.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial phenomena between lithium ion conductors and cathodes

Abstract: Nanocomposites of a lithium ion conductor Li1.3Al0.3Ti1.7(PO4)3 and electrode materials (TiO2 and FePO4) were prepared to investigate interfacial structure and ionic conductivity at the interface between the solid electrolyte and electrode materials. It was revealed that lithium ions in the solid electrolyte were attracted to the cathode materials with increasing electrode potential, which increases lithium vacancies in the solid electrolyte.For the FePO4 containing composites, due to the high electrode potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…We have so far studied the local structure at the interfacial region by fabricating nano-composites of active materials and solid electrolytes, and confirmed that the interfacial region with distorted lattice ranges for at least 20-50 nm in thickness [13,14].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…We have so far studied the local structure at the interfacial region by fabricating nano-composites of active materials and solid electrolytes, and confirmed that the interfacial region with distorted lattice ranges for at least 20-50 nm in thickness [13,14].…”
Section: Introductionmentioning
confidence: 72%
“…In addition, we observed that ball-milling of a poor ionic conductor (Li 2 SiO 3 , LSO) resulted in increase in ionic conductivity without change in activation energy [13,17]. This is interesting because size reduction of solid electrolyte particles generally increases grain boundary resistance, which is generally observed for high ionic conductor [14]. The enhanced ionic conductivity in the nano-LSO may be explained by three plausible mechanisms.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…As a result of the ion transfer, Li þ -depletion layer (space charge layer) is formed in the solid electrolytes [27]. The decreased Li þ in the solid electrolytes adjacent to the interface would result in the increased interfacial resistance [26]. This would be also applied for active materials solutions.…”
Section: Influence Of Br 2 On Solid Electrolytementioning
confidence: 99%
“…However, the poor ionic conductivity of SEs and the high interfacial resistance between SEs and electrodes are two drawbacks for solid state lithium ion batteries, which could lead to low power density and poor cycling performance of SSBs. [8] Recently, great progress has been made in improving the ionic conductivity of SEs. Kanno's group reported a lithium superionic conductor Li 10 GeP 2 S 12 with ionic conductivity of 10 À 2 S/cm, [9] which is comparable to a liquid electrolyte.…”
Section: Introductionmentioning
confidence: 99%